2022
DOI: 10.1038/s42005-022-00951-x
|View full text |Cite
|
Sign up to set email alerts
|

Metastable ferroelectricity driven by depolarization fields in ultrathin Hf0.5Zr0.5O2

Abstract: As ferroelectric Hf0.5Zr0.5O2 (HZO) thickness scales below 10 nm, the switching characteristics are severely distorted typically showing an antiferroelectric-like behavior (pinched hysteresis) with reduced remanent polarization. Using Landau-Ginsburg-Devonshire (LGD) theory for the analysis of the experimental results, it is shown here that, in thin (5 nm) HZO, depolarization fields drive the system in a stable paraelectric phase coexisting with a metastable ferroelectric one, which explains the pinched hyster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The coercive voltage V c is small, around 1 V, which suggests that the memory devices can be programmed at a rather low voltage of less than 2 V. Similar hysteresis characteristics are found for the reference devices fabricated on bulk Nb:SrTiO 3 as shown in Figure S5, Supporting Information. The P-V and field cycling ("wake-up") characteristics are similar to those previously obtained on Ge substrates [18] for the same HZO layer thickness. A frequency dependence of the P-V loops is observed (see Figure S6) where the coercive field E c (voltage V c ) increases with frequency f as Ε c = f 𝛽 , with 𝛽 ∼ 0.23 in agreement with theory [38] mainly applying to epitaxial or single crystal ferroelectrics.…”
Section: Ferroelectricity and Memory Characteristicssupporting
confidence: 81%
See 1 more Smart Citation
“…The coercive voltage V c is small, around 1 V, which suggests that the memory devices can be programmed at a rather low voltage of less than 2 V. Similar hysteresis characteristics are found for the reference devices fabricated on bulk Nb:SrTiO 3 as shown in Figure S5, Supporting Information. The P-V and field cycling ("wake-up") characteristics are similar to those previously obtained on Ge substrates [18] for the same HZO layer thickness. A frequency dependence of the P-V loops is observed (see Figure S6) where the coercive field E c (voltage V c ) increases with frequency f as Ε c = f 𝛽 , with 𝛽 ∼ 0.23 in agreement with theory [38] mainly applying to epitaxial or single crystal ferroelectrics.…”
Section: Ferroelectricity and Memory Characteristicssupporting
confidence: 81%
“…[14,15] However, the requirement for ultrathin (<5 nm) Hf 0.5 Zr 0.5 O 2 (HZO) is a big obstacle. Indeed, with few exceptions [16,17] ferroelectricity in thin HZO becomes metastable [18] or totally unstable below 5 nm due to a large depolarization field, hampering the fabrication of functional FTJs. On the other hand, thicker HZO near 10 nm brings the device out of the direct tunneling regime and leads to unfavorably high programming voltages [19] and a rather high energy consumption of up to 1.8 pJ per programming event.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that increasing U 0 from 2 cm min −1 to 5 cm min −1 does not cause significant variations in the piezoelectric response, only slightly reducing the scatter of the data as seen from the error bars. However, an increase of U 0 to 10 cm min −1 does result in an increase of the piezoelectric coefficient of d From d eff results, we rule out the effect of depolarization fields, as these are most noticeable in ferroelectric films with thicknesses below 10 nm where a stable paraelectric phase coexists with a metastable ferroelectric one, resulting in pinched hysteresis (resembling a double loop), as reported in [34,35]. There, the injection and trapping of charges into pre-existing interfacial defects during field cycling (wake-up) screens the depolarization field, stabilizing the ferroelectricity [34,35].…”
Section: Optimization Of the Withdrawal Speedmentioning
confidence: 53%
“…Ferroelectric-based materials, especially HfO 2 -based materials, have been widely studied for future non-volatile memories and logic devices because of the compatibility to CMOS (complementary metal oxide semiconductor) process [1][2][3][4][5][6][7]. Although HfO 2 film shows ferroelectricity itself, various dopants such as Zr, Al, Si, Gd are incorporated to the HfO 2 -based ferroelectric for boosting its ferroelectricity, such that Al-doped HfO 2 (HAO) film demonstrated its superior ferroelectricity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%